Teacher and Student Perceptions of Problem-Based Learning: A Comparative Analysis Across Educational Levels - Singgih Subiyantoro; Erika Laras Astutiningtyas; Krisdianto Hadiprasetyo; Isna Farahsanti; Andhika Ayu Wulandari (International Journal of Educational and Life Sciences, 2025)
This study aims to compare the perceptions of Problem-Based Learning (PBL) among teachers and students in elementary, middle, and high schools. Using a mixed-methods approach, surveys and interviews were conducted with 15 teachers and 45 students across various schools. The results indicate that while elementary school teachers and students generally have positive perceptions of PBL, middle school participants report mixed feelings, often citing difficulties in adapting to the new learning style. High school respondents appreciate the depth of understanding fostered by PBL but express concerns about time constraints and curriculum coverage. These findings highlight the need for tailored PBL implementations that consider the specific challenges and advantages at each educational level. This study contributes by providing insights into the practical applications of PBL and suggesting areas for future research to optimize its effectiveness across diverse learning environments.